The great escape [videorecording (Blu-Ray)] - McQueen, Steve, 1930-1980; Garner, James, 1928-2014; Attenborough, Richard; Bronson, Charles, 1921-2003; Coburn, James; Clavell, James; Sturges, John, 1910-1992; Pleasence, Donald; Burnett, W. R. (William Riley), 1899-1982; Donald, James, 1917-1993 (20th Century Fox Home Entertainment, 2013)
In 1943, the Germans opened Stalag Luft III, a maximum-security prisoner-of-war camp designed to hold even the craftiest escape artists. In doing so, however, the Nazis unwittingly assembled the finest escape team in military history, who worked on what became the largest prison breakout ever attempted.